PHYSICAL FITNESS LEVEL OF STUDENTS IN PENCAK SILAT EXTRACURRICULAR PROGRAMME IN GEDUNG AJI SUB-DISTRICT - Darmawan, Dandi Firman; Tohir, Ahmad; Sari, Yohana Bela Christian; Ariesna, Rachmat Dody (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2024)
This study aims to measure and determine the level of physical fitness in extracurricular pencak silat students. The approach used in this research is descriptive. The method used in this research is quantitative method. This research was conducted by students. The data in this study were obtained through the TKJI test. The results showed that the level of physical fitness of students who participated in extracurricular pencak silat students was in the excellent category 0 students or (0%), good category 0 students or (0%), moderate category 0 students or (0%), poor category 27 students or (88.8%), very poor category 3 students or (11.1%). The level of physical fitness of students who take part in extracurricular pencak silat students is mostly in the less category, namely 88.8%. This shows that the level of physical fitness of extracurricular pencak silat students is in the less category. The level of physical fitness is closely related to pencak silat extracurricular achievements, so teachers or extracurricular trainers should pay attention to training programmes for the quality of physical fitness as a support for achieving better student achievement. To researchers who will conduct similar research can continue this research by linking the achievements of students who take part in pencak silat extracurriculars to other variables